Implementasi Ilmu Filsafat Dalam Pembelajaran Geografi - Silcenak Apadjulu; Wa Ode Samlia; Hasim Hasim; Nawir Sune (Geosfera: Jurnal Penelitian Geografi, 2025)
This study aims to analyze the implementation of philosophy of science in geography education, particularly through the use of ontological, epistemological, and axiological dimensions as the foundation for developing content, methods, and assessment. Within the context of the Merdeka Curriculum and the strengthening of the Pancasila Student Profile, geography learning requires students not only to master spatial concepts but also to develop critical, reflective, and ethical awareness of human–environment relationships. This research employs a qualitative approach with a literature review design, drawing on books, journal articles, and policy documents related to philosophy of science, philosophy of geography, and geography education. The findings indicate that the ontological dimension helps teachers and students understand the nature of geographical objects of study such as space, place, and landscape as complex and dynamic realities. The epistemological dimension directs learning toward scientific processes of knowledge construction through observation, mapping, geospatial technologies, and critical inquiry. Meanwhile, the axiological dimension positions geography learning as a means of fostering social and environmental responsibility by promoting values of sustainability, spatial justice, and global citizenship. The implementation of philosophy of science in geography classrooms can be realized through problem-based learning, contextual project work, reflective dialogue, and the integration of ethical issues into the analysis of geospheric phenomena. The study recommends strengthening geography teachers’ philosophical literacy, developing teaching modules grounded in philosophy of science, and conducting further empirical research on the impact of philosophical approaches on students’ critical thinking skills and character development